VERS UNE SOCIETE RELATIONNELLE EN FRANCE : IMPACT ET DIVERGENCE AVEC UNE SOCIETE ORIENTEE PAR L’ECONOMIE ET LE PIB : LE CAS DE LA PROTECTION SOCIALE - Bertrand PAUGET; Martine PEYRARD-MOULARD (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This theoretical article based on economy and management is trying to underline the limits of the GDP as well as the limits of the gross national happiness. Our contribution is to look after a different way to look at the creation of the relations (in a positive or a negative way) in the process of the creation of the services.